Ultrasound-assisted structural characterization and properties of glycosylation-modified products of the British red kidney bean protein antioxidant peptide fractions - Fan, Xiaoyu; Li, Yurui; Cui, Suping (Frontiers in Nutrition, 2025)
IntroductionIn order to clarify the effects of glycosylation reaction under ultrasonic conditions on the in vitro antioxidant activity, structural properties and functional properties of the British red kidney bean protein antioxidant peptide fractions, the British red kidney bean protein antioxidant peptide fractions and glucose were used as raw materials.MethodsFour experimental groups were established: BHPs, US, GR, and US-GR. The study investigated the following characteristics among the treatment groups: grafting degree, browning degree, antioxidant activities (total antioxidant capacity, hydroxyl radical scavenging activity, DPPH radical scavenging activity, superoxide anion scavenging activity, reducing power), physicochemical properties (Free amino group content, Total and free sulfhydryl group content), structural characterization (atomic force microscopy (AFM), intrinsic fluorescence spectroscopy, surface hydrophobicity, circular dichroism spectroscopy (CD), fourier transform infrared spectroscopy (FTIR)), functional properties(solubility, foaming properties, emulsifying properties).ResultsThe results showed that the antioxidant activities of the ultrasound-assisted glycosylation products were significantly enhanced (P < 0.05) compared with those of the British red kidney bean protein antioxidant peptide fractions, with the greatest enhancement in reducing power (105.38%) and the smallest enhancement in the scavenging rate of superoxide anion radical scavenging activity (32.35%); the ultrasound-assisted glycosylation resulted in an increase in the degree of grafting by 36.16%, decreased free amino acid content by 33.58%, decreased total sulfhydryl content, increased free sulfhydryl groups, smaller 3D size distribution on mesoscopic scale, decreased endogenous fluorescence intensity and surface hydrophobicity, and decreased β-sheet content and increased random coils content.DiscussionThese results suggest that ultrasound promoted the interaction between the British red kidney bean protein antioxidant peptide fractions and the glucose glycosylation reaction. The products of ultrasound-assisted glycosylation had higher solubility, foaming and emulsification properties, which significantly improved the functional properties of the glycosylated products. The present research provides a basis for the ultrasound-assisted glycosylation of the British red kidney bean protein antioxidant peptide fractions.